ANALYSIS OF BASIC SCIENCE CONCEPTUAL UNDERSTANDING AMONG ELEMENTARY SCHOOL PROSPECTIVE TEACHERS: A GENDER PERSPECTIVE - Ibrahim; Bahtiar; Maimun, Maimun; Ni Made Yeni Suranti; Alimuddin, Nurkhaerat; Nurwahidah; Asri Fauzi (BIOCHEPHY: Journal of Science Education, 2024)
This research aims to analyze the understanding of basic concepts of Natural Sciences in prospective elementary school teachers by paying attention to gender differences. This research uses a quantitative approach with a survey method. Data is obtained through assessing the average score in four main materials: work and energy, moments of force and simple planes, ecosystems, and substances and their changes. The number of respondents in this study was 51 prospective elementary school teachers, consisting of 8 male and 43 female. The instrument used in this research is a multiple choice test. The research results show that there are significant variations between male and female teacher candidates. Male teacher candidates excel in material on work and energy as well as substances and their changes, while female teacher candidates show better performance in material on moments of force and simple planes and ecosystems.